Ice water content of Arctic, midlatitude, and tropical cirrus - Schiller, C.; Krämer, M.; Afchine, A.; Spelten, N.; Sitnikov, N. (Journal of Geophysical Research, 2008)
In situ measurements of total water have been obtained during several airborne field experiments in the Arctic (POLSTAR 1997 and 1998; EUPLEX/ENVISAT 2003), at midlatitudes (ENVISAT 2002, Cirrus 2003 and 2004, TROCCINOX 2005), and in the tropics (APE-THESEO 1999, TROCCINOX/ENVISAT 2005, SCOUT-O3 2005) in 52 flights in cirrus using the Julich Lyman-alpha fluorescence hygrometer FISH. For a subset of 28 flights, the measurements are complemented by gas phase measurements of H2O. From the data set obtained in these experiments, the ice water content (IWC) in cirrus clouds is derived using two different approaches and functions of the minimum, mean, median, and maximum IWC are provided. The data are analyzed as a function of temperature in the range 183-250 K for Arctic, midlatitudinal, and tropical regions thus extending previous climatologies to much lower temperatures and lower detectable IWC. For each temperature, IWC covers a broad band, decreasing with temperature over the whole temperature range. In the tropics, several events of enhanced ice water content are observed which are related to recent impact of convection.